Employee participation and assessment of an organizational change intervention: a three-wave study of total quality management - Coyle-Shapiro, Jacqueline A.M. (1999)
Amid the debates on total quality management (TQM), empirical investigations of the process of change have been largely neglected. This article examines the process of change involved in implementing TQM and employees' experience of participation, and it evaluates the impact of employee participation in TQM on their commitment to the organization. The research design involved a survey of employees in a U.K. manufacturing setting, with three measurement occasions: 6 months prior to and 9 months and 32 months after the introduction of TQM. The findings suggest that supervisory participative style is positively related to employee participation. The extent of employee participation is positively related to the assessment of the benefits of TQM. Furthermore, how employees assess the beneficial impact of TQM is more important in predicting subsequent participation in TQM than is their initial participation. Finally, no relationship is found between employee participation in TQM and organizational commitment. - Reproduced
Keywords: Performance appraisal; Workers participation; Organizational change; Total quality management